Analytical QFD model for strategic justification of advanced manufacturing technology. (1st December 2014) - Singh, Mandeep; Sarfaraz, Ahmad; Sarfaraz, Matin; Jenab, Kouroush
This study uses the information received from advanced manufacturing technology (AMT), analytical hierarchical process (AHP) and quality function deployment (QFD) literature, to provide a framework for company's implementing AMT. This paper suggests an integrated AHP-QFD methodology for the selection of AMT. The AHP-QFD methodology has been illustrated with an industrial example of an aerospace supplier company, trying to make a selection between three groups of advanced manufacturing technology, to keep up with the competition. In the approach multiple requirements are identified and then prioritised to suggest a selection between the three technologies.